Analisis Pengaruh Kualitas Pelayanan Perpustakaan Terhadap Kepuasan dan Hubungannya dengan Loyalitas Mahasiswa - Nurendah, Yulia; Mulyana, Mumuh (Jurnal Ilmiah Manajemen Kesatuan, 2013)
Library is the center of knowledge. Library is Services. No Library without any services. The Satisfaction of Library Member to be one of the objective of Library services. The objectives of research are to analyze the influence of library services quality to student’s satisfaction and to analyze the correlation the satisfaction to library members’ loyality The research was conducted in STIE Kesatuan Library with research populaton is STIE Kesatuan’s Students, from July to September 2012. The majority of respondents in this reasearch were Female, age 20 years, students of S1 Management, students of regular classes, the member of librabary since 2010, as well as doing loan collection library with occasional frequency. Approach to analyze the datas used Partial Least Square (PLS) using Smart-PLS 2.0 M. The First models Research of Library Service was established by the Physical Evidence, Reliability, Responsiveness, Assurance and Empathy variable. The variables are correlated to the Student Satisfaction and Loyalty variable. The results showed that the Physical Evidence, Empathy, Assurance, Reliability and Responsiveness explains the variability of service quality construct at strongly level at 66.53%. Physical evidence has no significant positive correlation to student’s satisfaction. Empathy has a positive significant effect on student satisfaction. Assurance has no significant negative relationship to student satisfaction. Reliability has no significant positive relationship to student satisfaction. Responsivenes has a significant positive relationship to student satisfaction. Student satisfaction variables can explain the variability Loyalty Students construct at a moderate level that is equal to 43.29%. Student satisfaction has a significant positive relationship to student loyalty. Keywords:service quality; satisfaction; loyalty; partial least square